Order effects and employment decisions: Experimental evidence from a nationwide program - Nicolas Ajzenman; Gregory Elacqua; Luana Marotta; Anne Sofie Westh Olsen (Inter-American Development Bank (IDB), 2021)
In this paper, we show that order effects operate in the context of high-stakes, real-world decisions: employment choices. We experimentally evaluate a nationwide program in Ecuador that changed the order of teaching vacancies on a job application platform in order to reduce teacher sorting (that is, lower-income students are more likely to attend schools with less qualified teachers). In the treatment arm, the platform showed hard-to-staff schools (institutions typically located in more vulnerable areas that normally have greater difficulty attracting teachers) first, while in the control group teaching vacancies were displayed in alphabetical order. In both arms, hard-to-staff schools were labeled with an icon and identical information was given to teachers. We find that a teacher in the treatment arm was more likely to apply to hard-to-staff schools, to rank them as their highest priority, and to be assigned to a job vacancy in one of these schools. The effects were not driven by inattentive, altruistic, or less-qualified teachers. The program has thus helped to reduce the unequal distribution of qualified teachers across schools of different socioeconomic backgrounds.
Keywords: I24; D91; I25; 330; Order Effects; Teacher sorting; Satisficing